Diarylureas: Repositioning from Antitumor to Antimicrobials or Multi-Target Agents against New Pandemics - Alessia Catalano; Domenico Iacopetta; Michele Pellegrino; Stefano Aquaro; Carlo Franchini; Maria Stefania Sinicropi (MDPI AG, 2021)
Antimicrobials have allowed medical advancements over several decades. However, the continuous emergence of antimicrobial resistance restricts efficacy in treating infectious diseases. In this context, the drug repositioning of already known biological active compounds to antimicrobials could represent a useful strategy. In 2002 and 2003, the SARS-CoV pandemic immobilized the Far East regions. However, the drug discovery attempts to study the virus have stopped after the crisis declined. Today's COVID-19 pandemic could probably have been avoided if those efforts against SARS-CoV had continued. Recently, a new coronavirus variant was identified in the UK. Because of this, the search for safe and potent antimicrobials and antivirals is urgent. Apart from antiviral treatment for severe cases of COVID-19, many patients with mild disease without pneumonia or moderate disease with pneumonia have received different classes of antibiotics. Diarylureas are tyrosine kinase inhibitors well known in the art as anticancer agents, which might be useful tools for a reposition as antimicrobials. The first to come onto the market as anticancer was sorafenib, followed by some other active molecules. For this interesting class of organic compounds antimicrobial, antiviral, antithrombotic, antimalarial, and anti-inflammatory properties have been reported in the literature. These numerous properties make these compounds interesting for a new possible pandemic considering that, as well as for other viral infections also for CoVID-19, a multitarget therapeutic strategy could be favorable. This review is meant to be an overview on diarylureas, focusing on their biological activities, not dwelling on the already known antitumor activity. Quite a lot of papers present in the literature underline and highlight the importance of these molecules as versatile scaffolds for the development of new and promising antimicrobials and multitarget agents against new pandemic events.